2021
DOI: 10.1177/17590914211037505
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Ferroptosis in the Pathogenesis of Ischemic Stroke: A New Therapeutic Target?

Abstract: Ischemic stroke is one of the main causes of high morbidity, mortality, and disability worldwide; however, the treatment methods are limited and do not always achieve satisfactory results. The pathogenesis of ischemic stroke is complex, defined by multiple mechanisms; among them, programmed death of neuronal cells plays a significant role. Ferroptosis is a novel type of regulated cell death characterized by iron redistribution or accumulation and increased lipid peroxidation in the membrane. Ferroptosis is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 184 publications
(190 reference statements)
1
44
0
1
Order By: Relevance
“…26 Targeting ferroptosis serves as a promising approach for treating ischemic stroke; however, the exact mechanisms linking ferroptosis and inflammation remain under investigation. 27 Indeed, microglial activation occurs within minutes after stroke. A defective microglial activation may increase infarction and apoptosis after stroke.…”
Section: Neuroinflammation Manifests Over An Extended Period Poststrokementioning
confidence: 99%
“…26 Targeting ferroptosis serves as a promising approach for treating ischemic stroke; however, the exact mechanisms linking ferroptosis and inflammation remain under investigation. 27 Indeed, microglial activation occurs within minutes after stroke. A defective microglial activation may increase infarction and apoptosis after stroke.…”
Section: Neuroinflammation Manifests Over An Extended Period Poststrokementioning
confidence: 99%
“…Unlike the mitochondrial morphology of other types of cell death, the shrunken mitochondria, increased membrane densities, reduced or disappeared mitochondria crista along with intact nucleus can be observed in ferroptosis under transmission electron microscopy [ 6 – 8 ]. The possible molecular mechanisms of ferroptosis involve abnormal iron metabolism, lipid peroxidation, and some critical enzymes (like GPX4) [ 9 ]. Although ferroptosis is first formally put forward in tumors [ 10 ], a growing body of work has demonstrated that it is also related to ischemic events, such as in intestinal, lung, and renal [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an iron-dependent and non-apoptotic regulatory cell death mechanism have been discovered and named ferroptosis ( Zhang et al, 2021 ). Ferroptosis is widely involved in the development of stroke, brain injury, and tumors ( Bu et al, 2021 ; Guan et al, 2021 ; Hu et al, 2021 ). However, iron is an essential reagent for normal physiological activities of cells, ferroptosis is distinguished from other forms of cell death such as apoptosis, necrosis, and autophagy by the lethal iron-dependent accumulation of lipid-based reactive oxygen species (ROS) ( Ye et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%